2018
DOI: 10.19044/esj.2018.v14n10p234
|View full text |Cite
|
Sign up to set email alerts
|

Initial Public Offerings Short and Long Term Performance of MENA Countries

Abstract: This study examines a comprehensive set of 162 Middle East and North Africa (MENA) Initial Public Offerings (IPO's) for the period [2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015], considered the first and most comprehensive data set investigated to date. Results confirmed that IPO performances are mixed among MENA countries classified into three groups. The first group comprises countries whose IPOs over-performed the Benchmark portfolio over the short-run, but underp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…As a result of the low-quality information that is not already available in the primary market compared to the secondary market, this paper concludes that IFRS will not be of any help to investors of the secondary market who are interested in the financial reports of firms that have already been listed. The interpretation of this insignificant result is reinforced by a variety of earlier research that emphasize the differences in information asymmetry among the secondary and primary markets (Ritter 1991;Sehgal and Singh 2008;Dong et al 2011;AlShiab 2018). The findings demonstrate that the abundance of information available on the secondary market has the potential to assist investors in initial public offering in calculating the reasonable valuation in the first year after the stock's listing, thereby diminishing the significance of the IFRS in this sector of the economy.…”
Section: Empirical Results and Discussionmentioning
confidence: 76%
“…As a result of the low-quality information that is not already available in the primary market compared to the secondary market, this paper concludes that IFRS will not be of any help to investors of the secondary market who are interested in the financial reports of firms that have already been listed. The interpretation of this insignificant result is reinforced by a variety of earlier research that emphasize the differences in information asymmetry among the secondary and primary markets (Ritter 1991;Sehgal and Singh 2008;Dong et al 2011;AlShiab 2018). The findings demonstrate that the abundance of information available on the secondary market has the potential to assist investors in initial public offering in calculating the reasonable valuation in the first year after the stock's listing, thereby diminishing the significance of the IFRS in this sector of the economy.…”
Section: Empirical Results and Discussionmentioning
confidence: 76%
“…For instance, Alanazi and Al-Zoubi (2015) found that IPO firms underperformed the All Share Index of Saudi Arabia by 8.92%, 24.17% and 28.15% for a one-, two- and three-year window, respectively. In contrast, AlShiab (2018) and Kamaludin and Zakaria (2018) provided empirical evidence showing that IPO firms listed in Saudi Arabia outperformed the Tadawul by 22% and 8.5% in 12 months, respectively.…”
Section: Literature Reviewmentioning
confidence: 95%
“…However, our best possible search reveals a scantiness of the research in Indian context that carry out a comparative analysis of IPOs given a stabilizing period. In the literature it is evident that the researchers (e.g., Kooli and Suret, 2004;Ahmad-Zaluki et al, 2007;Lizińska and Czapiewski, 2018;AlShiab, 2018;Kamaludin and Zakaria, 2019) have attempted to conduct a post-issue long-term performance of the IPOs. However, the studies are limited to market performance only using return and risk parameters.…”
Section: Research Gap and Contributions Of The Papermentioning
confidence: 99%